Does the Implementation of Corporate Social Responsibility Have An Effect toward Profitability? - et. al., Debbie Christine, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to find out how and how the Implementation of Corporate Social Responsibility (CSR) on Profitability (ROA) on Large Trading Sub Sector Companies listed in Indonesia Stock Exchange Period 2014-2016. The background of this research, there are several companies experiencing loss and decrease of profitability (ROA) during year 2014-2016. Research taking samples with non probability sampling, while the technique used is purposive sampling. This research is explanatory research with type of investigation are descriptive and verification. The analysis data used simple linear regression and processed using software Eviews 8 program. The result of research indicate that Corporate Responsibility research on profitability of large trading sub sector companies of production goods listed in Indonesia Stock Exchange in 2014-2016.